Kecerdasan Emosi, Kecerdasan Spiritual dan Agresivitas pada Remaja - Agung J., Dwi Bakhtiar (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract. Aggressivity is one of destructive behaviors and often occurs among adolescents. This study aimed to test the hipothesis there are negative correlations between emotional intelligence and spiritual intelligence with aggressive behaviors. Subjects of the study were 120 students of public senior high school Grogol Kediri East Java. Data were collected by scales of the three variables, and further analysed by regression technque and partial correlation. Results showed that the research hypotesis above could be confirmed. Adolescents with higher emosional intelligence and spiritual tended to lower in agressive behaviors.Keywords: emotional intelligence, spiritual intelligence, aggressive behavior